kajian Metakaolinisasi Terhadap Sintesa Zeolit 4A Dari Kaolin - Affandry Taufik; Fajril Akbar; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Zeolite 4A can be used as alternative for replacing phosphate as builder of detergen. It can be synthesized from calcined kaolin. Kaolin in its natural state is less reactive and difficult to form zeolite 4A, threfore kaolin needs to be activated through calcination process. Calcination of kaolin were studied in variation of temperatures from 500˚C, 600˚C, 700˚C, and 800˚C. Sodium aluminate and sodium silicate used as reactants in reaction process of synthesis zeolite 4A mixed in 1, 2 and 3 hours, then heated at 80˚C for 8 hours. The samples were characterized by infrared spectroscopy. A calcination temperature of 700˚C (2 hr) is the optimum for this kaolin to change into a reactive metakaolin which gives zeolite 4A with high crystallinity. Keywords: calcination, kaolin, metakaolin, synthesis, zeolite 4A